Immune-related gene expression in honey bee larva (Apis mellifera) exposed to plant extracts from Humulus lupulus with antimicrobial activity against Paenibacillus larvae - Giménez Martínez, Pablo Darian (2021)
American foulbrood caused by Paenibacillus larvae brings with it several problems on beekeepers for the use of synthetic antibiotics, likewise led to the appearance of resistant strains and the presence of chemical residues in the commercial products of the hive. In recent years, the use of natural compounds for the control of P. larvae has increased. Herein, we propose to determine the value of the Minimal Inhibitory Concentration (MIC) of a hydroalcoholic extract of Humulus lupulus (hop) leaves of Victoria variety on P. larvae strain, and to evaluate its toxicity and effect on the expression of three genes of the immune system on honey bee larvae. For the extract, the MIC value was 83.79 μg/mL. For larvae, the extract did not show toxicity, on the other hand presented a down-regulation in the gene expression for the three genes evaluated. The results obtained here are a first report on the evaluation in the effect of natural extracts on the expression of genes related to the immune system in bee larvae.